Impact of Custom Interface Widgets on User Efficiency in Content Navigation Platforms - Ravi Kiran Kanneganti (Eastasouth Institute, 2023)
The simplest unit of functionality of user interface with digital systems is interface widgets. In spite of their seeming simplicity, the type, location, and design reasoning to the background of such widgets is what defines the efficiency with which a user navigates material-dense sites. This research looks into adjusting the design properties of a widget to the features of user efficiency (time taken to complete a task, rate of errors and cognitive load). This study involves 120 subjects in an experimental design with mixed methods and on three content navigator platforms and it measures performance based on 5 forms of widgets which include menus, scrollable conglomerates, adaptive items, navigation aids and controller of forms. Findings reveal the reduction in task completion times is an average of 18.4 more in hierarchical structure than mixed-structure alternatives and that in adaptive promotion of widgets, the error rates were less by 21.3. There is also a reduction in the cognitive load as captured through the fixations of the eye which is significantly reduced in linear navigation settings. These represent some of the quantitative constructs that can support the current qualitative recommendations and add design specifications to web, mobile and embedded content platforms.